Undernutrition and associated factors among pregnant women in East Borena Zone, Liban District, Oromia regional state, Ethiopia - Godana Arero (Frontiers in Nutrition, 2022)
BackgroundUndernutrition is cellular imbalance between supply of nutrients, energy and body’s demand to ensure growth, maintenance, and specific function. However, there was no study conducted earlier on this topic in East Borena Zone.ObjectiveTo assess the prevalence of undernutrition and associated factors among pregnant women in East Borena Zone, Liban District.MethodA community-based cross-sectional study was conducted on 420 study participants from November 20 to December 2021. The systematic sampling technique and simple random sampling methods were used to select study participants. Data were double entered into Epi-info software version 7 and SPSS version 21 software for analysis. Descriptive statistics were used to describe the characteristics of study participants. Bivariate and multivariable logistic regressions were carried out to identify the association between independent and dependent variables by measuring the adjusted odds ratio and 95% confidence interval. P-values less than 0.05 were considered statistically significant.ResultsPrevalence of undernutrition among pregnant women was about (44.9%) of family monthly income [AOR = 8.72 (4.80, 15.83)], women’s decision-making autonomy [AOR = 0.40 (0.19, 0.82)], skipping meal [AOR = 2.62 (1.41, 4.89)], substance use [AOR = 2.01 (1.07, 3.77)], household food insecurity [AOR = 2.01 (1.06, 3.80)], lack of prenatal dietary advice [AOR = 2.73 (1.53, 4.89)], absence of household latrine [AOR = 9.23 (3.48, 24.46)], not participating health development army’s meeting at village level [AOR = 3.01 (1.57, 5.72)] and hand washing habit [AOR = 6.55 (3.02, 14.20)] had shown statistically significant association with undernutrition.ConclusionThe prevalence of undernutrition among pregnant women was high income. Women’s decision-making autonomy, skipping meals, substances use, household food insecurity, lack of prenatal dietary advice, poor hand washing habit, lack household of latrine, and not participation in health development army’s meeting were found to be predictors of the undernutrition.